Transformation of macrophages into myofibroblasts in fibrosis-related diseases: emerging biological concepts and potential mechanism - Li, Xiujun; Liu, Yuyan; Tang, Yongjun; Xia, Zhaoyi (Frontiers in Immunology, 2024)
Macrophage-myofibroblast transformation (MMT) transforms macrophages into myofibroblasts in a specific inflammation or injury microenvironment. MMT is an essential biological process in fibrosis-related diseases involving the lung, heart, kidney, liver, skeletal muscle, and other organs and tissues. This process consists of interacting with various cells and molecules and activating different signal transduction pathways. This review deeply discussed the molecular mechanism of MMT, clarified crucial signal pathways, multiple cytokines, and growth factors, and formed a complex regulatory network. Significantly, the critical role of transforming growth factor-β (TGF-β) and its downstream signaling pathways in this process were clarified. Furthermore, we discussed the significance of MMT in physiological and pathological conditions, such as pulmonary fibrosis and cardiac fibrosis. This review provides a new perspective for understanding the interaction between macrophages and myofibroblasts and new strategies and targets for the prevention and treatment of MMT in fibrotic diseases.